Silver Nanoparticles Effects on In Vitro Germination, Growth, and Biochemical Activity of Tomato, Radish, and Kale Seedlings - Tymoszuk, Alicja (Materials, 2021)
The interactions between nanoparticles and plant cells are still not sufficiently understood, and studies related to this subject are of scientific and practical importance. Silver nanoparticles (AgNPs) are one of the most commonly produced and used nanomaterials. This study aimed to investigate the influence of AgNPs applied at the concentrations of 0, 50, and 100 mg·L−1 during the process of in vitro germination as well as the biometric and biochemical parameters of developed seedlings in three vegetable species: Solanum lycopersicum L. ‘Poranek’, Raphanus sativus L. var. sativus ‘Ramona’, and Brassica oleracea var. sabellica ‘Nero di Toscana’. The application of AgNPs did not affect the germination efficiency; however, diverse results were reported for the growth and biochemical activity of the seedlings, depending on the species tested and the AgNPs concentration. Tomato seedlings treated with nanoparticles, particularly at 100 mg·L−1, had shorter shoots with lower fresh and dry weights and produced roots with lower fresh weight. Simultaneously, at the biochemical level, a decrease in the content of chlorophylls and carotenoids and an increase in the anthocyanins content and guaiacol peroxidase (GPOX) activity were reported. AgNPs-treated radish plants had shorter shoots of higher fresh and dry weight and longer roots with lower fresh weight. Treatment with 50 mg·L−1 and 100 mg·L−1 resulted in the highest and lowest accumulation of chlorophylls and carotenoids in the leaves, respectively; however, seedlings treated with 100 mg·L−1 produced less anthocyanins and polyphenols and exhibited lower GPOX activity. In kale, AgNPs-derived seedlings had a lower content of chlorophylls, carotenoids, and anthocyanins but higher GPOX activity of and were characterized by higher fresh and dry shoot weights and higher heterogeneous biometric parameters of the roots. The results of these experiments may be of great significance for broadening the scope of knowledge on the influence of AgNPs on plant cells and the micropropagation of the vegetable species. Future studies should be aimed at testing lower or even higher concentrations of AgNPs and other NPs and to evaluate the genetic stability of NPs-treated vegetable crops and their yielding efficiency.